Polypyrrole functionalized with FePcTSA for NO(2) sensor application - Paul, Santhosh; Joseph, Michael (Sensors and Actuators B-Chemical, 2009)
The nitrogen dioxide (NO(2)) sensing capability of polypyrrole (PPy) was enhanced dramatically after functionalized with iron(III)phthalocyanine-4,4',4 `',4'''-tetrasulfonic acid monosodium salt (FePcTSA). The incorporated phthalocyanine was confirmed by different characterization techniques such as UV-vis spectroscopy, FTIR, GFAAS, EDAX, etc. The resistance of the functionalized PPy decreased spontaneously during exposure to NO(2) gas at room temperature. This material exhibited excellent stability, reversibility, and reproducibility. The lowest response time (t(50)) thus obtained is 47 s with a highest response factor (Delta R/R(0) x 100) of 50.25. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chemical sensor; Fe(III)phthalocyanine tetrasulfonate; Nitrogen dioxide; polypyrrole